Penalaran Aljabar Siswa SMP dalam Menyelesaikan Soal Pola Bilangan Berbantuan GeoGebra - Salsadila Rahma Yuniarti; Abdul Haris Rosyidi (Universitas Negeri Surabaya, 2024)
This study aims to describe the algebraic reasoning students in solving number pattern-assisted GeoGebra. The subjects of this study are students at State Junior High Schools in Nganjuk. Data collection procedures through the assignment of algebraic reasoning and interviews. Data analysis refers to the Herbert and Brown (2000). The results showed that two students had differences in generalizing number patterns in the second method because there are no constan variabel (in this case color) as with the first method, one student was not successful in generalizing because there were many colors and there were no constant colors compared to the first method. However, both students were equally successful in generalizing the first method. Based on the research results, attention is needed regarding the influence of color position or the number of colors used in GeoGebra to help students generalize the pattern and determine an effective solution strategy by considering the many elements and color positions in each pattern.